Epidemiology of human dermatophytoses in Africa - (:unkn) unknown (My University, 2018)
In this critical literature review, we summarize the epidemiological trends of dermatophytoses reported in Africa. Our findings clearly emphasize the heavy burden of dermatophytosis in Africa. Tinea capitis is the primary clinical presentation of dermatophytosis in African children throughout the entire African continent. The disease affects more than 20% of school-age children in West Africa, while the prevalence ranges from 10% to more than 70% in other regions of Africa. In African adults, the presence of tinea corporis is the most frequent indicator of dermatophytosis. However, epidemiological studies have been primarily conducted on particular patient groups that are not representative of the general population. We examined dermatophyte species distribution patterns. We observed a predominance of anthropophilic dermatophytes, mainly T. violaceum, in the North and East of Africa and both T. soudanense and M. audouinii in the Western and Central regions of the continent. Interestingly, the zoophilic species, M. canis, has recently emerged in North and East Africa. Optimization of both mycology diagnosis capacities and epidemiological methodology would provide insight into the role that climate and other global aspects of the human environment play in dermatophyte epidemiology. We advocate that using a multisectoral and collaborative strategy would strengthen such future studies.
Keywords: African Research